Health plan choice in the Netherlands: restrictive health plans preferred by young and healthy individuals. Issue 3 (14th March 2017) - Bes, Romy E.; Curfs, Emile C.; Groenewegen, Peter P.; de Jong, Judith D.
Abstract: In a health care system based on managed competition, health insurers negotiate on quality and price with care providers and are allowed to offer restrictive health plans. It is crucial that enrolees who need care choose restrictive health plans, as otherwise health insurers cannot channel patients to contracted providers and they will lose their bargaining power in negotiations with providers. We aim to explain enrolees' choice of a restrictive health plan in exchange for a lower premium. In 2014 an online survey with an experimental design was conducted on members of an access panel (response 78%; n =3, 417). Results showed 37.4% of respondents willing to choose a restrictive health plan in exchange for a lower premium. This fell to 22% when the restrictive health plan also included a longer travelling time. Enrolees who choose a restrictive health plan are younger and healthier, or on lower incomes, than those preferring a non-restrictive one. This means that enrolees who use care will be unlikely to choose a restrictive health plan and, therefore, health insurers will not be able to channel them to contracted care providers. This undermines the goals of the health care system based on managed competition.